Polarized light in liquid crystals and polymers - Scharf, Toralf (Wiley-Interscience, 2007)
Polarized Light in Liquid Crystals and Polymers deals with the linear optics of birefringent materials, such as liquid crystals and polymers, and surveys light propagation in such media with special attention to applications. It is unique in treating light propagation in micro- and nanostructured birefringent optical elements, such as lenses and gratings composed of birefringent materials, as well as the spatial varying anisotropic structures often found in miniaturized liquid crystal devices.